Preparation of carrier-free phosphorus-32 - Aleta, Carlito R. (1965)
Two methods of preparing carrier-free P-32 from irradiated sulfur were studied in an attempt to gain information about the future P-32 production by PARC (Philippine Atomic Research Center). One method is solid-liquid extraction using water as solvent and 2-octanol as wetting-agent; the other is liquid-liquid extraction using a mixture of glacial acetic acid and acetic anhydride (3:1 by volume) as solvent.